METHODS FOR THE DETECTION OF INTERNAL DISEASES (American Journal of Interdisciplinary Research and Development, 2024)
The abstract should provide a concise summary of the article, including the significance of accurate detection methods in diagnosing internal diseases and an overview of the methods discussed.